SURVEYING OBSERVATIONS OF THE DEFORMATION OF SLOPES IN PITS - Xakimova, Sabina Zaynitdin qizi; Davronova, Gulchehra Jurabek qizi; Abruyev, Samandar Shodmon o‘g‘li; To‘xtashev , Alisher Bahodirovich (Innovative Development in Educational Activities, 2023)
To the article the prevention of landslides and collapses of slopes at quarries, as well as development of measures to reduce harmful impact of deformations of ledges, sides, dumps and territories adjacent to quarries, is a prerequisite for uninterrupted operation of the mining enterprise.